Tax Aggressiveness Affected by CSR, Capital Intensity, Inventory Intensity, Intengible Assets in Transportation Companies - Suryarini, Trisni; Hajawiyah, Ain; Munawaroh, Siti (Jurnal Dinamika Akuntansi, 2021)
Purpose: The purpose of this study is to determine whether tax aggressiveness is influenced by CSR, capital intensity, inventory intensity and intangible assets. Tax aggressiveness is one of the tax planning schemes. The act of tax aggressiveness is not only caused by the behaviour of the taxpayer’s noncompliance with tax regulations but can also be caused by the taxpayer’s desire to make tax-saving in accordance with the regulations.Method: The sample was selected using a purposive samplings technique with the result of 31 transportation companies listed on the Indonesia Stock Exchange from 2016 to 2019. The analysis method used in this research is multiple regression analysis.Findings: The results obtained indicate that the hypotheses put forward three hypotheses were accepted and one was rejected. Capital Intensity has a positive effect on tax aggressiveness, Inventory Intensity has a negative effect on tax aggressiveness, Intangible Asset has a positive effect on tax aggressiveness, the results are accepted. Corporate Social Responsibility disclosure has a negative effect on tax aggressiveness, the results rejected.Novelty: The study reveals that tax aggressiveness can support intangible assets in transportation companies. The Currently developing transportation company is not owned by the company.